Effect of sodium fluoride in chlorhexidine mouthwashes on force decay and permanent deformation of orthodontic elastomeric chain - Sufarnap, Erliera; Harahap, Kholidina Imanda; Terry, Terry (Padjadjaran Journal of Dentistry, 2021)
Introduction: Orthodontic elastomeric chain is polyurethane elastomer that is widely used among orthodontists due to its functions. Chlorhexidine (CHX) and sodium fluoride (NaF) are listed in mouthwash composition which could affect the mechanical properties of the elastomeric chain. This study was aimed to analyze the effect of sodium fluoride in chlorhexidine mouthwashes on force decay and permanent deformation of orthodontic elastomeric chains. Methods: This research is an experimental analytic laboratory with pretest-posttest control group design. 150 samples of orthodontic chains were divided into three groups. Group 1: artificial saliva (control group); Group 2: 0,1% chlorhexidine gluconate solution (CHX); Group 3: 0,1% chlorhexidine digluconate with sodium fluoride solution (CHX-NaF). The orthodontic elastomeric chain was stretched and maintained at a standardized distance equivalent to a force of 300 g. The measurement of force decay and permanent deformation were performed with digital force gauge and digital caliper (0.01mm) at intervals of the first, seventh, fourteenth, twenty-first, and twenty-eighth days, respectively. Results: The force decay and permanent deformation of the elastomeric chain compared among three groups (control, CHX mouthwash and CHX+NaF mouthwash) showed did not have any significantly different (p-value>0,05) at the first, seventh, fourteenth, twenty-first, and twenty-eighth days, respectively. Conclusion: Sodium fluoride in chlorhexidine mouthwash showing no difference among saliva, CHX mouthwash and CHX+NaF mouthwash on force decay and permanent deformation of elastomeric chain.